Two theories of the subprime crisis: governance failure or mere greed?. (1st January 2013) - Gordon, Cameron
This paper examines two theories of the 'subprime crisis' or 'GFC'. The 'financial architecture' theory holds that the failure of the financial system was fundamentally driven by institutional faults, especially in private sector risk management and public sector regulation and underpins the system reform approaches currently being taken by much of the developed world. The other theory, referred to as the 'inevitability school' here, emphasises the irrational aspects of human behaviour and complex systems which lead to inevitable cycles and collapses. This paper provides a framework for assessing the relative merit of these two theories in explaining the current crisis and then applies that framework to existing evidence focusing on the role that institutional governance failure may have played. The general conclusion is that both schools explain parts of the crisis, but that institutional reforms are likely to have relatively little preventive effect beyond the short to medium term.